Quality of Randomized Controlled Trials for Surgical Treatment of Carpal Tunnel Syndrome: A Systematic Review. Issue 3 (March 2019) - Long, Chao; Azad, Amee D.; desJardins-Park, Heather E.; Fox, Paige M.
Abstract : Background: Randomized controlled trials are considered the gold standard in evidence-based medicine. The authors conducted a systematic review to evaluate the quantity, quality, and trends of randomized controlled trials that assess surgical treatment of carpal tunnel syndrome. Methods: The authors identified randomized controlled trials comparing two or more surgical interventions for carpal tunnel syndrome in PubMed, Cochrane, Scopus, Google Scholar, and Clinicaltrials.gov. Two independent reviewers evaluated articles for inclusion, extracted data, and assessed randomized controlled trial quality using the Jadad score. Results: Of 2253 identified studies, 58 met full inclusion criteria. They were published between 1985 and 2015, with a significant increase over time ( p = 0.003). They were most frequently published in Journal of Hand Surgery (European Volume ) [ n = 15 (25.9 percent)]. Most randomized controlled trials were single-center studies [ n = 54 (93.1 percent)] conducted in the United Kingdom [ n = 13 (22.4 percent)] or the United States [ n = 10 (17.2 percent)], with a mean study size of 80.1 ± 55.5 patients. Funding source was unknown in 62.1 percent ( n = 36). Three-quarters [ n = 44 (75.9 percent)] of randomized controlled trials did not define the primary outcome measure(s). Less than 30 percent ( n = 17) of randomized controlled trials conducted a power analysis. Only four studies with patients reported lost to follow-up provided an explanation for each patient. Six randomized controlled trials (10.3 percent) conducted intention-to-treat analysis. The mean Jadad score was 2.14 ± 1.26, with no significant improvement over time ( p = 0.245). Conclusions: Despite the significant increase in the number of randomized controlled trials published studying surgical treatment of carpal tunnel syndrome over time, a mean Jadad score of 2.14 with no change over time indicates a need for improvement in quality. Proper study design is key to avoiding introduction of bias and ensuring the validity of conclusions drawn. Abstract : Supplemental Digital Content is available in the text.